Enhancing Competitiveness of Jalerpitu MSME through Legal and Digital Support - Defi Tristio Putri; Shafira Niken Sari; Indah Novita Sari; Nadia Salsa Bila; Rizka Syahira Ramadhani; Kharisma Laila Ismawati (Universitas Nurul Jadid, 2026)
This mentoring program was carried out to assist the Jalerpitu folding table MSME in Mentoro Village, Soko District, Tuban Regency in obtaining business legality, improving digital marketing capabilities, and strengthening brand identity. The main problems faced by the partner include the absence of a Business Identification Number (NIB), low digital literacy, and suboptimal promotion strategies through online media. This program employs the Participatory Action Research (PAR) approach, which positions the business owner as an active subject throughout the entire mentoring process. Through the stages of diagnosis, joint planning, action, and reflection, the facilitators and partners work collaboratively to design and implement solutions according to the real needs of the business. The activities include training and technical assistance in building brand identity through logo and banner design, registration of the NIB through the OSS (Online Single Submission) system, as well as the creation and management of a Shopee account as a digital marketing platform. The entire process is implemented through hands-on learning to ensure the partner can understand and independently repeat each step. The results of the mentoring show a significant increase in the partner's understanding of legal procedures, ability to use digital platforms, and application of marketing strategies through online marketplaces. The development of a more consistent brand identity also enhances product appeal and business visibility. Overall, the application of the PAR approach has proven effective in encouraging active partner involvement, strengthening business capacity, and expanding market sustainably